Detectability of common ravens (Corvus corax) in the eastern USA: Rapid assessment of a recolonizing species. Issue 6 (15th June 2022) - Hackworth, Zachary J.; Felch, Joshua M.; Murphy, Sean M.; Cox, John J.
Abstract: Common ravens ( Corvus corax ) inhabited much of the eastern United States prior to European colonization but were nearly extirpated by the mid‐1900s. Although remnant raven populations have since begun recolonizing portions of their historic range in the eastern United States, the extent of recovery remains largely unknown because of the species' elusive behavior. To aid development of targeted monitoring programs for this rare and cryptic species, we investigated factors that may influence detectability of ravens in natural cliff habitat during the nesting season in the Central Appalachian Mountains. Using a time‐to‐detection framework, we performed surveys at cliff sites with positive raven occupancy and recorded time to first detection (TFD) and confirmed cliff occupancy (i.e., occupied detection) to estimate detection probability curves as a function of survey time. We further compared multiscale habitat features of occupied and unoccupied cliff sites to characterize regional nesting habitat. Mean TFD at occupied cliffs was 14 ± 2 (SE) min. The TFD and subsequent detection probability increased with warming temperatures, likely as a result of heightened activity at nests as the reproductive season progressed. Shorter distances from observation point to the surveyed cliff resulted in longer TFD, indicating that ravens are likely sensitive to disturbance at nest sites. Analysis of cliff‐nesting habitat data identified raven selection of cliffs with large, exposed faces positioned on predominant west‐facing aspects. Mean detection probability calculated from detectability curves was ≥0.8 after the first 30 min. Using a probability‐based model and empirical detection probabilities, we estimated that raven absence from a cliff site during the nesting season may be inferred with p = 0.99 after three independent 30‐min surveys. Although ravens have been considered elusive and rare in the eastern United States, we find that their detectability at occupied cliff sites during the nesting season is relatively high and that observation of distributional changes may be easier for this species than for other, more cryptic birds.